Analisis Semiotika Pesan Komunikasi dalam Film Siksa Kubur Karya Joko Anwar - Abi, Faisal; Choiriyati, Sri; Azizah, Meylin (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
This study analyzes communication messages in the film Siksa Kubur (Joko Anwar, 2024) using John Fiske’s semiotic framework, which divides texts into three levels of codes: reality, representation, and ideology. Employing a qualitative descriptive method, data were obtained through intensive observation of the film, documentation of key scenes, and literature review from scholarly works and critics’ reviews. The findings reveal the complexity of the relationship between religion, trauma, and power as represented in the film. At the reality level, the suicide bomber, pesantren power relations, and Sita’s transformation are portrayed through physical details, behaviors, and expressions. At the representation level, cinematic techniques such as camera, lighting, sound, and editing reinforce the horror atmosphere and highlight unequal social relations. At the ideological level, the film exposes the manipulation of religion as a justification for violence, the normalization of sexual abuse, and personal trauma leading to a crisis of faith. This study concludes that Siksa Kubur is not merely a horror entertainment but also a social critique and religious reflection on how religion can operate both as an instrument of control and a source of trauma.